Adsorption of O2 on anionic silver clusters: spins and electron binding energies dominate in the range up to nano sizes. Issue 2 (30th November 2015) - Ma, Jun; Cao, Xizi; Xing, Xiaopeng; Wang, Xuefeng; Parks, Joel H.
Abstract : Exploring the reactivity of metal clusters is an important task in cluster science, while only a few previous studies involve the reactions of nano-sized ones. Abstract : Exploring the reactivity of metal clusters is an important task in cluster science, while only a few previous studies involve the reactions of nano-sized ones. Here we report a kinetic measurement on reactions of Ag n − ( n = 6–69) with O2 using a flow reactor running at 120 K. Their relative rates were obtained by fitting decay processes of parent ions at different O2 flow rates. Comparing the variations of the kinetic rates and the photodetachment energies of Ag n − ( i.e. the binding energies of their excess electrons), we distinguished the separate effect of clusters' spins or their electron binding strength. This work firstly shows that reactions of O2 and Ag n − up to nano sizes are still dominated by the clusters' global electronic properties. This conclusion is conceptually important for understanding the reaction mechanisms on silver based nanocatalysts.